Coincidence of Events Causing Paradoxical Hypotension in a Patient with an Intra-Aortic Balloon Pump - Muhammad Atif Masood Noori; Hardik Fichadiya; Hasham Saeed; Qirat Jawed; Shruti Jesani; Asnia Latif; Meherwan Joshi (European Journal of Case Reports in Internal Medicine, 2022)
The left ventricular outflow tract is a region of the left ventricle that lies between the anterior leaflet of the mitral valve and the ventricular septum. Dynamic left ventricular outflow tract obstruction (LVOTO) has classically been observed in patients with hypertrophic obstructive cardiomyopathy (HOCM) where it occurs secondary to asymmetric septal hypertrophy and systolic anterior motion (SAM) of the mitral valve. However, there are some instances that lead to hypercontractility of the myocardium, and with a combination of other physiological conditions, result in SAM of a mitral valve leaflet, leading to LVOTO in the absence of phenotype. We present such a case of an acute inferolateral wall myocardial infarction that was complicated by cardiogenic shock, requiring an intra-aortic balloon pump (IABP) and inotropic support which paradoxically provoked LVOTO. A reduction in IABP counterpulsation from 1:1 to 1:3 and the addition of intravenous fluids and a beta blocker resulted in significant improvement in blood pressure with rapid tapering of pressors. Inotropes and IABP, although helpful in cardiogenic shock, have the potential to induce or worsen the LVOTO, which can lead to a vicious cycle of worsening hypotension and increasing adrenergic drive that further deteriorates myocardial viability. Timely diagnosis with an echocardiogram and the withdrawal of inotropic and IABP support has the potential to improve haemodynamics and, thereby, outcome.